IMPROVING THE LABOR MARKET TRADE-OFF BETWEEN INFLATION AND UNEMPLOYMENT* - Holt, Charles C. (American Economic Review, 2016)
The work on the Phillips curve has been predominantly empirical, but policy intervention designed to decrease both inflation and unemployment requires a better theoretical understanding of the determinants of this relation. This paper attempts to sketch out the basic labor market relationships that appear to the author to account largely for the Phillips relation2 and then to consider the kinds of policy measures that this analysis suggests are relevant for moving the Phillips curve. The basic issue involved in the stability or instability of the Phillips curve when the inflation rate is constant is explored with a simple model in the appendix. The emphasis in this paper is on the atomistic operation of the labor market because it appears sufficient to generate the Phillips relation, but we do not deny that union bargaining and price dynamics may also be involved to some degree. This paper concentrates on conceptual issues. Continuing research will be devoted to the statistical measurement of relationships.